AN APPLICATION OF BHAVANA PRINCIPLE TO ENHANCE THE WELL-BEING OF THE ELDERLY OF TROKPLA COMMUNITY, MUEANG TRANG DISTRICT, TRANG PROVINCE - Thiravachiro (Jaitrong), Phra Thawatchai; ., Phrakru Kositwattananukul; ., Phrakru Wijitsilajarn; ., Phrakru Wijitsaturot (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to 1) to study the concept of enhancing the well-being of the elderly; 2) to investigate the Bhavana principle in the Theravada Buddhist scriptures, and 3) to apply the principles of Bhavana to enhance the well-being of the elderly. It is qualitative research focusing on documents and in-depth interviews. Findings were as follows: In the research, it was found that: 1) Concept of Enhancing Elderly well-being is the process of achieving physical and mental integrity with physical aspects consisting of physical strength, social aspects consisting of good interaction with others. Pertaining to mental, there is simple happiness and for wisdom, there is concept to perceive human beings with understanding to harmoniously live with awareness according to reality. 2) The Bhavana principle in Theravada Buddhist scriptures is a principle that develops oneself to be prosperous both physically and mentally. There are four aspects: 2.1) Kaya-bhavana: physical development known to consume four factors, 2.2) Sila bhavana: behavior development moral development to live in society, 2.3) Citta-bhavana: cultivation of the heart to accommodate the emotions and flourish with virtue, 2.4) Panna-bhavana: solve problems with wisdom cultivation of wisdom of elders’ life with a process of deliberation all things as they really are. 3) The application of Bhavana principle to enhance elders’ well-being of Trokpla community, Muang Trang district is used in the four aspects: 3.1) Kaya-bhavana: making elders physically strong, 3.2) Sila bhavana: promoting elders in building relationship with family, community and society, 3.3) Citta-bhavana: enhancing elders with positive attitude and morality, 3.4) Panna-bhavana: promoting elders with life understanding and thinking process with awareness according to reality.